2019
DOI: 10.1039/c9ra06509a
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation as a green method to enhance the dielectric behaviour, magnetization, antibacterial activity and dye removal capacity of Co–Fe LDH nanosheets

Abstract: Nowadays, improving the physico-chemical properties of nanomaterials to enhance their performance towards various applications is urgent. Accordingly, gamma irradiation (GI) has evolved and attracted wide attention as a promising green technique to meet this need. In the current study, a Co-Fe LDH was used as a model 2D nanomaterial and was irradiated by GI (dose ¼ 100 kGy). The sample was characterized via XRD, FTIR, FESEM, HRTEM, hydrodynamic size, zeta potential, and BET surface area measurements. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The peaks at 3425 cm −1 can be ascribed to the OH stretching vibration and bending, respectively. 32 …”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 3425 cm −1 can be ascribed to the OH stretching vibration and bending, respectively. 32 …”
Section: Resultsmentioning
confidence: 99%
“…The crystallinity index can also be calculated from the area of a specific region such as the 900-1200 cm −1 wavenumber range which is widely known as the spectrum/peak due to the This journal is © Royal Society of Chemistry and IChemE 2022 v 1 and v 3 normal vibrational modes. To estimate CI area-1060 using this technique, a baseline range was selected from 900 to 1200 cm −1 wavenumbers and presented as eqn (19).…”
Section: Height ¼mentioning
confidence: 99%
“…A 1060 A 900-1200 (19) where A 1060 and A 900-1200 denote the areas of the mentioned peak and region, respectively. Another area near 603 cm −1 was selected to compute the crystallinity index area-603 ) measuring the total area (A 1 ) and the splitting area (A 2 ) for the phosphate group, and mathematically presented as eqn (20).…”
Section: Area-1060 ¼mentioning
confidence: 99%
See 1 more Smart Citation
“…The prepared LDH showed high removal percent for heavy metals in wastewater along with excellent antimicrobial behavior. Amin et al prepared Gamma irradiated CoFe LDH and reported good antibacterial activity against both Gram-positive and Gram-negative bacteria strains along with high removal of malachite green (MG) and methylene blue (MB) dyes 27 . Zaher et al reported the promising antibacterial properties and oxytetracycline hydrochloride removal capacities of ZnFe LDH nano-adsorbent 28 .…”
Section: Introductionmentioning
confidence: 99%